Serial Interval and Generation Interval for Imported and Local Infectors, Respectively, Estimated Using Reported Contact-Tracing Data of COVID-19 in China - Li, Menghui; Liu, Kai; Song, Yukun; Wang, Ming; Wu, Jinshan (Frontiers in Public Health, 2021)
The emerging virus, COVID-19, has caused a massive outbreak worldwide. Based on the publicly available contact-tracing data, we identified $509$ transmission chains from $20$ provinces in China and estimated the serial interval (SI) and generation interval (GI) of COVID-19 in China. Inspired by possibly different values of the time-varying reproduction number for the imported cases and the local cases in China, we divided all transmission events into three subsets: imported (the zeroth generation) infecting 1st-generation locals, 1st-generation locals infecting 2nd-generation locals, and others transmissions among $2+$. The corresponding SI (GI) is respectively denoted as $SI^{0}_{1}$($GI^{0}_{1}$), $SI^{1}_{2}$ ($GI^{1}_{2}$), and $SI^{2+}_{3+}$($GI^{2+}_{3+}$). A Bayesian approach with doubly interval-censored likelihood is employed to fit the distribution function of the SI and GI. It is found that the estimated $SI^{0}_{1}=6.52\left(95%CI: 5.96-7.13\right)$, $SI^{1}_{2}=6.01\left(95%CI: 5.44-6.64\right)$, $SI^{2+}_{3+}=4.39\left(95%CI: 3.74-5.15\right)$, and $GI^{0}_{1}=5.47\left(95%CI: 4.57-6.45\right)$, $GI^{1}_{2}=5.01\left(95%CI: 3.58-7.06\right)$, $GI^{2+}_{3+}=4.25 \left(95%CI: 2.82-6.23\right)$. Thus overall both SI and GI decrease when generation increases.